Boom and busts: Consumption, house prices and expectations - Orazio P. Attanasio; Laura Blow; Robert Hamilton; Andrew Leicester (Institute for Fiscal Studies (IFS), 2005)
Over much of the past 25 years, the cycles of house price and consumption growth have been closely synchronised. Three main hypotheses for this co-movement have been proposed in the literature. First, that an increase in house prices raises households' wealth, particularly for those in a position to trade down the housing ladder, which increases their desired level of expenditure. Second, that house price growth increases the collateral available to homeowners, reducing credit constraints and thereby facilitating higher consumption. And third, that house prices and consumption have tended to be influenced by common factors. This paper finds that the relationship between house prices and consumption is stronger for younger than older households, which appears to contradict the wealth channel. These findings therefore suggest that common causality has been the most important factor behind the link between house price and consumption.
Keywords: C13; D10; D91; E21; 330; House prices; consumption booms; wealth effects; collateral effects; common causality